Pengelolaan Sumber Daya Laut Antarbatas Negara: Tantangan Bagi Indonesia sebagai Negara Maritim - Andi Sumar Karman (Antropologi Indonesia, 2014)
This aritcle discusses about the phenomenon of globalization involving two fishermencommunities, the Tomalou fishermen in Tidore islands and the Philipines fishermen. Bothof them sail and hunt in the same seawater zone, constructed and formed as a transborderterritory between Indonesia and the Philipines. The natural resources management systemthrough decentralization should ensure the exsistence of local fishermen (Tomalou) to gainmarine (fish) resources, secured by government without interference by the Philipine fishermen.The data in this paper has been analyzed with several transborder theories. As a result, thispaper shows that the state representated by the regional government has failed to protect thelocal fishermen (Tomalou) and ensure in continued presence in achiving welfare from the searesources.Keywords: Globalization, The Tomalou Fishermen, Decentralization, Transborder studies